A highly sensitive colorimetric and ratiometric fluorescent probe based on 3-hydroxyphthalimide for detection of Hg2+ in aqueous solution and its application in real sample analysis. Issue 9 (27th February 2020) - Yang, Binying; Huang, Jing; Bao, Cheng; Zhang, Shishen; Han, Yifeng
Graphical abstract: Highlights: A new and ESIPT-based fluorescent probe for Hg 2+ has been designed and developed. The probe exhibits high sensitivity and fast kinetics for Hg 2+ ions in aqueous solution. The probe was successfully used to rapidly detect Hg 2+ ions in real water samples. Abstract: A new and simple ESIPT-based water-soluble fluorescent chemodosimeter MS7 for the efficient colorimetric and ratiometric detection of mercury ions have been rationally designed and developed. Based on the specific reactivity of mercury-promoted intramolecular ring-closed reaction, the probe exhibits high selectivity, excellent sensitivity, and fast kinetics for mercury ions in almost pure aqueous solution (containing only 1% DMSO) with a low detection limit of 1.73 ppb. Furthermore, the manufacture of probe test strips was achieved to facilitate visual inspection of Hg 2+ ions. Moreover, the probe has also been successfully applied to the detection of Hg 2+ ions in different real water samples with satisfactory results, indicating that the probe might be a potential and feasible method for detecting Hg 2+ in ecosystems.